Architecture and Fresco Decoration Programs in Novgorod’s Monastic Churches / Об особенностях архитектуры и программ фресковой декорации монастырских церквей Новгорода второй половины XIV века - Tatiana Tsarevskaya / Татьяна Юрьевна Царевская (Визуальная теология, 2024)
Studying architecture and frescoes of Novgorod’s monastic churches of the second half of the 14th century, one has to face the fact that the purpose of some annexes as well as internal compartments is yet unknown and their liturgical function remains unclear. Our insufficient understanding of ‘architectural iconography’ of these additional spaces complicates the interpretation of the murals with all their semantic nuances. Monastic churches of Novgorod had a tendency to gradually phase out external extensions while increasing the partitioning of the western part of the nave. In this article we attempt to clarify the purpose of these new spaces using the example of Novgorod’s suburban monastic churches and to characterize the programs of their fresco decorations assuming multifaceted function of these extra spaces, including their symbolic significance. The iconographic program of the narthex in the Assumption Church in archbishop’s Volotovo monastery served as a kind of a prelude to the decoration of the main space and corresponded to the beginning of the Assumption evening service following the traditions of Palaeologan Renaissance. A less ‘theological’ program of the narthex of the Church of the Savior in Kovalevo monastery whose ktetors were Novgorod boyars, emphasized the connection between the healing of body and soul with salvation in Christ, indicating adherence to local liturgical traditions as well as the influence of the Western Balkans’ artistic culture. But, despite the differences in traditions, both decorative programs of the vestibules prepared the faithful for the entry into the main space of the church as into the House of Divine Wisdom. The character of female images in these monasteries correlated with the type of a monastery: Volotovo was a male monastery, while Kovalevo, most probably, was of the mixed type. An unusual location of the monastic theme in the painting of the choir of another suburban monastic church, Nativity in the Red Field, is, in our opinion, linked to the purpose of its associated monastery which served a large cemetery. При исследовании росписей новгородских монастырских храмов второй половины XIV века приходится сталкиваться с тем, что назначение внешних пристроек и отдельных внутренних компартиментов, их функционирование в богослужебном контексте всё ещё представляются нечётко. Такая неразработанность архитектурной «иконографии» дополнительных пространств осложняет понимание многослойности содержания росписей и их смысловых оттенков. Монастырские храмы Новгорода в этом плане бывали устроены весьма своеобразно и неодинаково, но имели тенденцию к редуцированию пристроек и, напротив, к увеличению западной части основного объёма. В статье делается попытка уточнить назначение этих пространств на примере новгородских загородных монастырских храмов, имевших роспись, и кратко охарактеризовать специфику фресковой декорации (там, где она сохранилась) исходя из полифункционального характера этих архитектурных частей и их символики. Более «учёная» программа росписи притвора церкви Успения в архиепископском Волотове монастыре служила своего рода увертюрой к декорации основного объёма и точно соответствовала началу вечерней службы на храмовый праздник Успения, наследуя традиции палеологовского ренессанса. Более демократичная программа притвора церкви Спаса в монастыре на Ковалёве, ктиторами которого были бояре, акцентировала тему связи исцеления тела и души со Спасением во Христе, указывая на приверженность местной традиции почитания и, вместе с тем, на знакомство с художественной культурой западных Балкан. Но, несмотря на различие традиций, декоративным программам притворов в равной степени свойственно приготовление входящего в основной объём храма как в мир средоточия Премудрости. Состав женских изображений в этих памятниках позволяет говорить о характере монастырей: в случае Волотова – мужского, Ковалёва – вероятно, смешанного. Особенность локализации монастырской тематики в росписи на хорах церкви ещё одного загородного монастыря – Рождества на Красном поле – обусловлена, на наш взгляд, спецификой монастыря, обслуживавшего большое кладбище.